Research and implementation of unified monitoring system for multi-datacenters - Baojun JIA; Lei XU; Yuhua GUO; Wei XIONG; Sufen LI (Dianxin kexue)
A monitoring system solution of supporting multi-datacenter and multiple private cloud environments were proposed.In order to achieve load balancing and easy scale-out，the unified monitoring system adopted a distributed framework and encapsulated Zabbix API and OpenStack API.This solution was significant for the study of similar distributed cluster scheduling system.